Pioglitazone increases the glycolytic efficiency of human Sertoli cells with possible implications for spermatogenesis. (October 2016) - Meneses, M.J.; Bernardino, R.L.; Sá, R.; Silva, J.; Barros, A.; Sousa, M.; Silva, B.M.; Oliveira, P.F.; Alves, M.G.
Abstract: Pioglitazone is a synthetic agonist for the nuclear receptor peroxisome proliferator-activated receptor γ used to treat type 2 diabetes mellitus. Recently we reported that antidiabetic drugs regulate the nutritional support of spermatogenesis by Sertoli cells. Herein, we investigate the effects of pioglitazone on human Sertoli cells metabolism. Human Sertoli cells were cultured in the presence of pioglitazone (1, 10, 100 μM). Protein levels of phosphofructokinase 1, lactate dehydrogenase, hexokinase, glucose transporters (GLUT1, GLUT2, GLUT3), monocarboxylate transporter 4 and oxidative phosphorylation complexes were determined by Western blot. Lactate dehydrogenase and alanine aminotransferase activity were assessed and metabolite production and consumption determined by proton nuclear magnetic resonance. Mitochondrial membrane potential was also determined. Glucose consumption more than doubled in human Sertoli cells stimulated with pioglitazone 100 μM. Mitochondrial complex II protein levels increased 50% with exposure to pioglitazone (100 μM) in human Sertoli cells, though mitochondrial membrane potential was decreased by 32%. The pharmacological concentration of pioglitazone (10 μM) almost doubled lactate production and established crucial correlations among key intervenient of glycolysis. Moreover, in the same concentration, alanine aminotransferase decreased more than 80%. Our results suggest that pioglitazone (10 μM) increases the efficiency of the glycolytic flux and lactate production by human Sertoli cells, which is essential to sustain and preserve the spermatogenic event. Thus, pioglitazone may improve male fertility and thus, be considered a suitable antidiabetic drug for men in reproductive age.